2017
DOI: 10.1007/s00775-017-1520-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective tuning of activity in a multifunctional enzyme as revealed in the F21W mutant of dehaloperoxidase B from Amphitrite ornata

Abstract: Possessing both peroxidase and peroxygenase activities with a broad substrate profile that includes phenols, indoles, and pyrroles, the enzyme dehaloperoxidase (DHP) from Amphitrite ornata is a multifunctional catalytic hemoglobin that challenges many of the assumptions behind the well-established structure-function paradigm in hemoproteins. While previous studies have demonstrated that the F21W variant leads to attenuated peroxidase activity in DHP, here we have studied the impact of this mutation on peroxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…S10. Multiple previous structures of DHP-B have been determined under cryogenic conditions (de Serrano et al, 2010;McCombs, Moreno-Chicano et al, 20.17;Carey et al, 2018). Despite the B factors being smaller for structures determined at 100 K compared with those reported at RT here, the overall structural features are maintained.…”
Section: Comparison Of Overall Structuresmentioning
confidence: 55%
“…S10. Multiple previous structures of DHP-B have been determined under cryogenic conditions (de Serrano et al, 2010;McCombs, Moreno-Chicano et al, 20.17;Carey et al, 2018). Despite the B factors being smaller for structures determined at 100 K compared with those reported at RT here, the overall structural features are maintained.…”
Section: Comparison Of Overall Structuresmentioning
confidence: 55%
“…Recently, Ghiladi and coworkers [62] showed that DHP B exhibited a catalytic efficiency (k cat /K m ) of 2,100 M −1 Sec −1 in oxidation of 2,4,6-TCP, which is 10-fold higher than that of WT DHP A ( Table 2). Replacement of Phe21 in the heme distal site of DHP B by Trp was found to decrease the catalytic efficiency by 7.2-fold, and more pronounced effect (decreased by 15fold) was observed for the F21W mutation in DHP A (Table 2) [63].…”
Section: Comparison Of the Kinetic Parameters For H 2 O 2 -Dependent mentioning
confidence: 92%
“…Non-His-tagged DHP B was overexpressed and purified as described in the literature. ,, DHP B crystals were obtained using the hanging-drop vapor diffusion method. The crystals were grown from mother liquor solutions of 32% PEG 3350 and 0.2 M ammonium sulfate at pH 6.4 and equilibrated against identical reservoir solutions.…”
Section: Methodsmentioning
confidence: 99%
“…These peroxide-activated forms of DHP initially return to the ferric resting state upon substrate oxidation, although further reduction to oxyferrous DHP has been noted under some conditions. 24,25,34,40,41 Given the diverse functions (O 2 carrier, peroxidase, peroxygenase, and oxidase) exhibited by DHP across this broad panel of substrates, we have previously suggested that the substrate itself can act to modulate enzyme activity in DHP, 29,30 with binding/orientation (relative to the ferryl iron), pK a , and redox potential all being key determinants in terms of which mechanism leads to substrate oxidation. More interestingly, however, it also appears that substituent effects may play a pseudoallosteric role (Figure 1): the peroxidase substrate phenol is converted to a peroxygenase substrate upon addition of a 4-nitro substituent, 34 whereas 4-Br-phenol is an inhibitor 42 of peroxidase and peroxygenase activities in DHP.…”
mentioning
confidence: 99%
See 1 more Smart Citation